Mistiming of thought and perception predicts delusionality - Bear, Adam (Proc Natl Acad Sci U S A, 2017)
The timing of thoughts and perceptions plays an essential role in belief formation. Just as people can experience in-the-moment perceptual illusions, however, they can also be deceived about how events unfold in time. Here, we consider how a particular type of temporal distortion, in which the apparent future influences “earlier” events in conscious awareness, might affect people’s most fundamental beliefs about themselves and the world. Making use of a task that has been shown to elicit such reversals in the temporal experience of prediction and observation, we find that people who are more prone to think that they predicted an event that they actually already observed are also more likely to report holding delusion-like beliefs. Moreover, this relationship appears to be specific to how people experience prediction and is not explained by domain-general deficits in temporal discrimination. These findings may help uncover low-level perceptual mechanisms underlying delusional belief or schizotypy more broadly and may ultimately prove useful as a tool for identifying those at risk for psychotic illness.